Distinct complication profiles: a comparative study of Ethiopian and non-Ethiopian adults with type 1 diabetes - Kirzhner, Alena; Bashkin, Amir; Green, Hefziba; Abu Khadija, Haitham; Teitlboim, Shay; Zikry Deitch, Meital; Alnees, Mohammad; Greenstein, Merav; Schiller, Tal (Frontiers in Endocrinology, 2025)
AimsEthiopian ethnicity is linked to a higher risk of diabetes, yet data on disease characteristics and complications in Ethiopians with type 1 diabetes (T1D) are limited. This study aimed to assess clinical features and complication rates in Ethiopian versus non-Ethiopian T1D patients.MethodsThis population-based retrospective cohort study included all patients insured in Clalit Health Services (CHS) who were considered to have T1D according to study criteria between January 1, 2000, and December 31, 2022. Patients were followed until December 31, 2023, for the development of composites of microvascular and macrovascular complications.ResultsAmong 12,759 T1D patients, 672 (5.3%) were Ethiopian, and 4,375 (34%) were diagnosed before age 18. The mean age was 30.4 years, 54% were male, and the mean BMI was 25.4 kg/m². Average follow-up was 10.9 years. In multivariable Cox regression models, Ethiopian ethnicity was an independent risk factor for microvascular complications (hazard ratio [HR] 1.325; 95% CI 1.124–1.563; p = 0.001) but was associated with a lower risk of macrovascular complications (HR 0.606; 95% CI 0.425–0.863; p < 0.001).ConclusionsThe striking differences in diabetes-associated complications underscore the need for ethnic-specific and population-specific follow-up, therapeutic, and preventive approaches for T1D patients.